Best Answer

3x - 2y and 3x + 2y are in their simplest form. They don't factor.

Q: What are the factors of 3x-2y and 3x 2y?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

3x = 2y + 7 The standard form is: 3x - 2y - 7 = 0

It is 14*(3x + 2y)

(3x - 2y)(9x^2 + 6xy + 4y^2)

Solve the simultaneous equations by eliminating one of the variables and solving for the other variable, substitute the found value back into one of the equations to solve for the eliminated variable, and then substitute both values found into the other equation as a check:3x + 2y = 5x + 2y = 7{1} - {2} â†’ (3x - x) + (2y - 2y) = 5 - 7 â†’ 2x = -2As there is 27 in both equations, subtract one from the other ({1}-{2}) and then solve {3}2x = -2â†’ x = -1Substituting back into equation {2}:x + 2y = 7-1 + 2y = 7â†’ 2y = 8â†’ y = 4Checking by substituting for x and y in {1}:3x + 2y = 53Ã—-1 + 2Ã—4 = -3 + 8 = 5 as requiredâ†’ The required solution is x = -1, y = 4.

If that's -9x^3 - 3x^2 + 3x + 1, that factors to (1 - 3x^2)(1 + 3x)

Related questions

3x times 2y = 3x2y In a system of equations, you can only solve for a system if there are the same amount of variables as equations. Since there is only one equation (actually, it is a monomial, but considering 3x2y=0) and there are two variables, x and y, we cannot solve for the variables. The simplest form is 3x2y.

3x times 2y=3x2y. Without the measurements of x and y it is impossible to answer that math problem any further, so in the future, include the measurements of x and y,if any,in your question.

2y-6=3x2y-3x-6=0-3x-6=-2y3/2x+3=yy-inercept= 3slope= y(2)-y(1)/x(2)-x(1)= 6-3/2-0= 3/2

Since there are no common factors, just multiply everything: 3x times 2y = 6xy

3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3

3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3

3x plus 2y can be expressed mathematically as (3x + 2y).

(3x-2y)2=

(3x-2y)2=

-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5

4x-2y+3x+2y When simplified: 7x

-3x + 2y = 12-3x + 3x + 2y = 3x + 122y = 3x + 122y/2 = 3x/2 + 12/2y = (3/2)x + 6